A facile route to bespoke macro- and mesoporous block copolymer microparticles - He, Guping; Bennett, Thomas M.; Alauhdin, Mohammad; Fay, Michael W.; Liu, Xin; Schwab, Simon T.; Sun, Cheng-gong; Howdle, Steven M. (Royal Society of Chemistry, 2018)
We report a facile and versatile strategy for the bespoke fabrication of macro- and mesoporous block copolymer microparticles. A clean synthetic route, RAFT dispersion polymerisation in supercritical carbon dioxide (scCO2), is used to generate block copolymer microparticles. Selective swelling/deswelling is then applied to induce controlled morphology transitions and to trap the resulting porous state. The pore sizes are controllable over a large size range (~20 – 200 nm) by varying the length of the swellable block. Through a systematic approach we then demonstrate that the shape of the pores can also be tailored from isolated spheres through to interconnected/bicontinuous channels by varying the ratio of the two blocks. This process is shown to be applicable to a range of poly(methyl methacrylate) (PMMA)based block copolymer systems, including PMMA-b-poly(4-vinyl pyridine), PMMAb-poly(dimethyl acrylamide) (DMA) and PMMA-bpoly(dimethylaminoethylmethacrylate) (DMAEMA). In each case, the second minority block (e.g. P4VP, etc.) was selectively swollen with an alcohol to induce an order-toorder morphology transition and then quenched rapidly by the non-solvent hexane. This not only takes place on the order of hours, but is also freely scalable for the production of grams of material and beyond in a single step following polymerisation.